Synthesis of Zirconia Nanoparticles and Their Ameliorative Roles as Additives Concrete Structures - Masoud Negahdary; Amir Habibi-Tamijani; Asadollah Asadi; Saeid Ayati (Journal of Chemistry)
We investigated synthesis of zirconia nanoparticles (Nps) and their ameliorative roles as additives concrete structures. Synthesized Zirconia Nps were studied with X-ray diffraction (XRD), UV-visible spectrophotometer, and transmission electron microscope (TEM). We used standard Portland cement in related experiment Concrete Structures. The experimental or E series (E1–E4) mixtures were prepared with different amounts of ZrO2 Nps with an average particle size of 20 nm. The experimental mixtures were prepared 0.125, 0.25, 0.5 and 2.0% ZrO2 Nps/cement by weight. The modified cement with ZrO2 nanoparticles was studied with split tensile strength, flexural strength and setting time methods. Final results showed that Zirconia Nps could be used for their Ameliorative roles as Additives Concrete Structures.